2020
DOI: 10.1097/md.0000000000021644
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sjögren syndrome-associated acute interstitial nephritis and type 3 renal tubular acidosis in a patient with thin basement membrane nephropathy

Abstract: Introduction: The kidney is one of the common extraglandular sites involved in primary Sjögren syndrome (pSS), with chronic tubulointerstitial nephritis (TIN) the most common pathology type. Renal involvement in pSS often presents as chronic TIN accompanied by type 1 or 2 renal tubular acidosis (RTA). Description of renal involvement as acute TIN with type III RTA in pSS has been rarely reported. Patient concerns: A 37-year-old woman was admitted with complaints of dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…This network provides additional information through new components, such as a chain of transitive causal relationships, mediators, and confounders of existing relationships through triangular structures. Through this causal network, we have observed that Tubulointerstitial nephritis is the most common renal disease caused by Sjögren's syndrome and may lead to renal tubular acidosis (RTA) , which in turn may cause osteomalacia [56] , [57] . Even though the entire sequence chain was not directly observed in the data we used, the network could weave the individual relationships and create a more holistic view of the knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…This network provides additional information through new components, such as a chain of transitive causal relationships, mediators, and confounders of existing relationships through triangular structures. Through this causal network, we have observed that Tubulointerstitial nephritis is the most common renal disease caused by Sjögren's syndrome and may lead to renal tubular acidosis (RTA) , which in turn may cause osteomalacia [56] , [57] . Even though the entire sequence chain was not directly observed in the data we used, the network could weave the individual relationships and create a more holistic view of the knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…However, the treatment is very much dependent upon disease progression [ 164 ]. For the most common renal manifestations, especially in severe or active interstitial nephritis, treatment with systemic corticosteroids is recommended [ 172 ]. During disease relapse, a steroid-sparing agent is required, and AZA [ 172 ] or MMF [ 173 ] have been used with success.…”
Section: Extraglandular Manifestationsmentioning
confidence: 99%
“…Aiming for a better understanding of the disease, we performed a search of the PubMed database using MeSH descriptors (Acidosis, Renal Tubular; Lupus Erythematosus, Systemic; Sjogren’s Syndrome, Systemic Vasculitis, Rheumatoid Vasculitis, Arthritis, Rheumatoid, Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis, Churg-Strauss Syndrome, IgA Vasculitis, Spondylitis, Ankylosing, Cryoglobulins, Hepatitis, Autoimmune, Liver Cirrhosis, Biliary), and we identified 37 individual case reports published since December 2016 with the association of distal renal tubular acidosis and the following autoimmune disorders: SLE, Sjögren’s syndrome, autoimmune hepatitis, primary biliary cirrhosis and rheumatoid arthritis (see Table 1 ) [ 6 , 10 , 11 , 13 , 15 , 16 , 17 , 18 , 20 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. We also identified a case of hereditary autoimmune polyendocrine syndrome (DRTA, hypoparathyroidism, Addison disease), published in a series of cases, which was not included in our analysis, due to the lack of individual data availability [ 39 ].…”
Section: Epidemiology Clinical Presentation and Diagnosismentioning
confidence: 99%
“…After 4 years of treatment, eGFR improved from 46 mL/min/1.73 m 2 to 71 mL/min/1.73 m 2 and the patient no longer needed oral potassium and alkali supplements suggesting that DRTA might respond to Rituximab. Another immunosuppressive drug used for two patients was mycophenolate-mofetil, without signs of DRTA improvement [ 17 , 33 ]. In only one case out of these 33 reports, cyclophosphamide was used, with eGFR improvement and potassium value amelioration [ 33 ].…”
Section: Treatment and Outcomementioning
confidence: 99%
See 1 more Smart Citation